2019
DOI: 10.7150/jca.30757
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-17-5p promotes angiogenesis in nasopharyngeal carcinoma via targeting BAMBI

Abstract: Objective: The purpose of our study is to investigate the role of miR-17-5p in angiogenesis of nasopharyngeal carcinoma and the crosstalk between HUVECs and CNE-2 via exosomes.Methods: Firstly, flow cytometry, cell viability assay, transwell assay, and tube formation were used to explore the role of miR-17-5p in angiogenesis. Then zebrafish model was used to confirm effects of miR-17-5p on angiogenesis. qRT-PCR analysis and Immunofluorescence assay were used to explore the expression of miR-17-5p in NPC tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…For example, reduced expression of miR-542-3p could inhibit VEGF signaling by increasing IGFBP1 (a negative regulator of VRGFR2 activation) ( Zhang et al, 2012 ; Tochigi et al, 2017 ). Reduced expression of miR-17-5p can increase the levels of BAMBI ( Duan et al, 2019 ), a negative regulator of AKT signaling that is involved in PAC migration and proliferation ( Zheng et al, 2007 ). Likewise, reduced expression of miR-31-5p could increase Satb2 levels and promote apoptotic death ( Lian et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, reduced expression of miR-542-3p could inhibit VEGF signaling by increasing IGFBP1 (a negative regulator of VRGFR2 activation) ( Zhang et al, 2012 ; Tochigi et al, 2017 ). Reduced expression of miR-17-5p can increase the levels of BAMBI ( Duan et al, 2019 ), a negative regulator of AKT signaling that is involved in PAC migration and proliferation ( Zheng et al, 2007 ). Likewise, reduced expression of miR-31-5p could increase Satb2 levels and promote apoptotic death ( Lian et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our present longitudinal study showed significant differences in plasma miRNA profile between persons who succeed and who failed in both periods of the study: at Baseline and after 6 months. Compared with smokers, quitters showed significant downregulation of important miRNAs (miR-17, miR-20a, miR-20b, miR-93 and miR-125) enrolled in nasopharyngeal carcinogenesis 45 , lung cancer [46][47][48][49] , metastasis and cisplatin-resistance 50 , when over-expressed through different signal pathway-mediated mechanisms. These differences in plasma miRNA profiles between the two groups remained after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miRNAs are capable of regulating lymphangiogenesis and angiogenesis within the primary tumour and at metastatic sites ( Table 1 ). Within a tumour, most exosomal miRNAs are considered to be produced by tumour cells and, when internalised by endothelial cells, some of these miRNAs can stimulate angiogenesis and/or lymphangiogenesis by repressing the expression of proteins that inhibit the main pathways that drive these processes [ 64 , 65 , 66 ]. Exosomal miRNAs have been shown to down-regulate several anti-angiogenic transcription factors in endothelial cells, and thereby initiate the angiogenic switch [ 24 , 67 , 68 ], or to repress inhibitors of the expression of VEGFA, a key inducer of angiogenesis.…”
Section: Role Of Exosome-derived Non-coding Rnas In Tumour Lymphanmentioning
confidence: 99%